Assessment of Quality of Life of Doctors during Corona Pandemic in a Tertiary Hospital in Dhaka City - Md Shariful Haque,; Mohammad Shamsul Ahsan,; Md Shahedul Islam,; Rubaiya Khan,; Bijoy Kumar Dutta,; Jhowhar Datta,; Tanvir Rahman Shah, (Journal of Comilla Medical College Teachers' Association, 2024)
Background: Corona pandemic is an event where there is a rupture of the normal life pattern. The healthcare professionals specially doctors had faced an unknown potential threat to life that made them work in an intense and fearful situation. So, their quality of life (QOL) was affected in that pandemic. Objectives: To assess the physical health, psychological, social relationship, and environmental domains of quality of life of doctors during COVID-19 pandemic in a tertiary level hospital. Methods: It was a cross sectional study that included 100 doctors who were working during corona pandemic in BSMMU. Then they were interviewed with a semi-structured socio-demographic questionnaire. Quality of life was assessed by validated Bengali version of World Health Organization quality of life scale brief (WHOQOL-BREF). Data analysis was performed by statistical package for social science (SPSS), version-20. Results: Among the four domains, the environmental domain had the lowest score followed by physical health and psychological health domain and the social relationship domain showed a relatively higher score. Besides, environmental health scores of female doctors were significantly higher than those of male doctors. Perceptions of quality of life were significantly poor among doctors who were in current economic struggle (p=0.034) or in fear of future economic struggle (p=0.009). Score of environmental health domain were significantly low among doctors who were in current economic struggle (p=0.0137) as well as in fear of future economic struggle (p=0.015). Conclusion: All domains of quality of life were impaired in doctors during COVID-19 pandemic situation. Among the four domains of WHOQOL-BREF scale, environmental domain was mostly affected. Environmental health of male doctors was worse than female doctors during COVID-19 pandemic. Current as well as fear of future economic struggle in COVID-19 pandemic detrimentally affected perception of quality of life among responded doctors. These also caused poor environmental health among doctors in COVID-19 pandemic. J Com Med Col Teachers Asso Jan 2024; 28(1): 09-13